Whole cell reconstructions of Leishmania mexicana through the cell cycle - Hair, Molly; Yanase, Ryuji; Moreira-Leite, Flávia; Wheeler, Richard John; Sádlová, Jovana; Volf, Petr; Vaughan, Sue; Sunter, Jack Daniel (PLoS pathogens, 2024)
The unicellular parasite Leishmania has a precisely defined cell architecture that is inherited by each subsequent generation, requiring a highly coordinated pattern of duplication and segregation of organelles and cytoskeletal structures. A framework of nuclear division and morphological changes is known from light microscopy, yet this has limited resolution and the intrinsic organisation of organelles within the cell body and their manner of duplication and inheritance is unknown. Using volume electron microscopy approaches, we have produced three-dimensional reconstructions of different promastigote cell cycle stages to give a spatial and quantitative overview of organelle positioning, division and inheritance. The first morphological indications seen in our dataset that a new cell cycle had begun were the assembly of a new flagellum, the duplication of the contractile vacuole and the increase in volume of the nucleus and kinetoplast. We showed that the progression of the cytokinesis furrow created a specific pattern of membrane indentations, while our analysis of sub-pellicular microtubule organisation indicated that there is likely a preferred site of new microtubule insertion. The daughter cells retained these indentations in their cell body for a period post-abscission. By comparing cultured and sand fly derived promastigotes, we found an increase in the number and overall volume of lipid droplets in the promastigotes from the sand fly, reflecting a change in their metabolism to ensure transmissibility to the mammalian host. Our insights into the cell cycle mechanics of Leishmania will support future molecular cell biology analyses of these parasites.
Keywords: Cell Cycle; Leishmania mexicana; Psychodidae; Leishmania; savci; buněčný cyklus; Animals; paraziti; Parasites; Cell Division; Mammals; buněčné dělení; zvířata